2016
DOI: 10.1371/journal.pone.0145895
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Progesterone Levels on the Day of Oocyte Maturation May Affect Top Quality Embryo IVF Cycles

Abstract: In contrast to the impact of elevated progesterone on endometrial receptivity, the data on whether increased progesterone levels affects the quality of embryos is still limited. This study retrospectively enrolled 4,236 fresh in vitro fertilization (IVF) cycles and sought to determine whether increased progesterone is associated with adverse outcomes with regard to top quality embryos (TQE). The results showed that the TQE rate significantly correlated with progesterone levels on the day of human chorionic gon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
92
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(104 citation statements)
references
References 29 publications
8
92
3
1
Order By: Relevance
“…Our results thus extend the observation of two recent studies focused on Day 3 embryos [1516] and deserve further research.…”
Section: Resultssupporting
confidence: 89%
“…Our results thus extend the observation of two recent studies focused on Day 3 embryos [1516] and deserve further research.…”
Section: Resultssupporting
confidence: 89%
“…7,11,12,2023,34 However, in our own data we observed a linear relationship between serum progesterone and live birth so we conclude that it is not possible to report a threshold above which we observe a significantly reduced live birth rate. Instead, we observed a steady decline in live birth rate with increasing progesterone.…”
Section: Which Progesterone Level Is Detrimental?contrasting
confidence: 72%
“…Although previous studies and a metaanalysis (Melo et al, 2006;Shapiro et al, 2010;Venetis et al, 2013) have shown that progesterone elevation in the late follicular phase has no adverse effect on oocyte and embryo quality, suggesting that elevated exposure of the developing follicles to progestins is safe, several recent publications have challenged this concept. Elevated progesterone concentrations on the day of oocyte maturation induction have in fact been said to significantly reduce the formation rate of top-quality blastocysts (Huang et al, 2016;Vanni et al, 2017). Progesterone elevation on the day of HCG administration has been said also to adversely affect the cumulative live birth rate per oocyte retrieval cycle (Bu et al, 2014), even if this result seems more dependent on the detrimental effect of progestin on the endometrium.…”
Section: Advantages and Disadvantages Of Progestins In Ovarian Stimulmentioning
confidence: 99%